1981
DOI: 10.1007/bf00268758
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Drosophila flightless mutants which affect myofibrillar proteins of indirect flight muscle

Abstract: A large number of dominant flightless mutants of Drosophila were chemically induced, and their thorax proteins were examined by chemically induced, and their thorax proteins were examined by means of two-dimensional gel electrophoresis (O'Farrell 1975). Among them, 26 lines were found to have deficiency or reduction of some of myofibrillar proteins in indirect flight muscle (IFM). The gel patterns of the mutants could be classified into eleven groups. In general, more than a few polypeptides were either absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 23 publications
8
112
0
Order By: Relevance
“…The absence of myosin light chains in these mutants is consistent with a defect in a thick filament protein that results in the turnover of other thick filament-asso ciated proteins, due to lack of thick filament assembly [for a discussion of pleiotropic effects of contractile pro tein gene mutations, see Mogami and Hotta (1981)]. The failure to accumulate known thick filament proteins, in conjunction with the genetic recombination and mutant rescue data, strongly suggested that the mutations are defects within the MHC gene that result in the under production of MHC protein.…”
Section: Contiactile Piotein Accumulation In the Homozygous-viable Mumentioning
confidence: 78%
See 4 more Smart Citations
“…The absence of myosin light chains in these mutants is consistent with a defect in a thick filament protein that results in the turnover of other thick filament-asso ciated proteins, due to lack of thick filament assembly [for a discussion of pleiotropic effects of contractile pro tein gene mutations, see Mogami and Hotta (1981)]. The failure to accumulate known thick filament proteins, in conjunction with the genetic recombination and mutant rescue data, strongly suggested that the mutations are defects within the MHC gene that result in the under production of MHC protein.…”
Section: Contiactile Piotein Accumulation In the Homozygous-viable Mumentioning
confidence: 78%
“…This suggests that the mutations are hypomorphic and do not result in the production of a neomorphic gene product that blocks muscle function in the presence of two wild-type alleles. Mogami and Hotta (1981) previously examined protein accumulation in thoraces of Mhc^ [formerly called Ifm(2)2] by two-dimensional gel electrophoresis. They found that two myosin light chains (spots 138, 185), as well as additional proteins (spots 158, 159), were missing and proteins 33 and 74 were reduced.…”
Section: Genetic Mapping Of the Homozygous-viable Mutantsmentioning
confidence: 99%
See 3 more Smart Citations